Pilgrims of Woodstock : Never-Before-Seen Photos. - Kane, John (Professor of media arts) (Red Lightning Books, 2019)
Pilgrims of Woodstock offers a vivid and intimate portrait of the overlooked stars of the festival: the everyday people who made Woodstock unforgettable. Experience the real and unedited Woodstock through Richard Bellak's never-before-seen photographs and John Kane's incredible new interviews.